Construction of pLLO vector encoding truncated form of Listeriolysin O as molecular adjuvant for DNA vaccine studies - Pouriayevali, Mohammad Hassan; Bamdad, Taravat; Sadat, Seyed Mehdi; Sabahi, Farzaneh; Aghasadeghi, Mohammad Reza (Archives of Medical Laboratory Sciences, 2019)
Background: The major problem of DNA vaccine is less immunogenicity of them verses other killed or live whole organism vaccines therefore adjuvants for use in this kind vaccines is very necessary. Genetic adjuvants with bacterial sources are an appropriate approach to modulate immune responses to DNA vaccines. Listeria Monocytogenes proteins such as Listeriolysin O (LLO) with CD4 and CD8 epitopes can be as an adjuvant to initiate both innate and adaptive immune responses if the protein cytotoxicity can be eliminated. Herein we constructed a truncated LLO plasmid as genetic adjuvant and tested it in combination with a DNA construct as a model vaccine. Materials and Methods: About 1340bp of the 5’ end of whole LLO gene was amplified by PCR on DNA purified from Listeria Monocytogenes. Sequential sub cloning of truncated LLO into the Xho I/EcoRV sites of pcDNA3.1 plasmid, downstream of CMV promoter was done. pLLO plasmid was transfected to HEK293T cell line by lipofection method. LLO protein expression from transiently transfected 293T cell lysates was confirmed by western blotting. Then the adjuvant activity of LLO in BALB/c mice model was analyzed using proliferation test. Results: Double digestion of pLLO plasmid with the enzymes that were applied for cloning led to the isolation of two fragments with expected sizes. The final plasmid was also confirmed following sequencing reactions. Moreover, expression of LLO was evidenced in transfected 293T cells, compared to non-transfected controls. In vivo study was shown, high significant proliferative responses in LLO co-immunization pattern. Conclusion: In the DNA vaccine study, LLO co-administration plasmid could be a suitable genetic adjuvant to enhance cellular immune response of vaccine.